Population Composition and Ectoparasite Prevalence on Bats (Sturnira ludovici; Phyllostomidae) in Forest Fragments and Coffee Plantations of Central Veracruz, Mexico. (14th November 2012) - Saldaña‐Vázquez, Romeo A.; Castro‐Luna, Alejandro A.; Sandoval‐Ruiz, Cesar A.; Hernández‐Montero, Jesús R.; Stoner, Kathryn E.
Abstract Studies comparing the abundance of frugivorous bats in shade‐coffee plantations and forest fragments report contradictory results, and have not taken into account the landscape context in which coffee plantations are immersed. Variables of population composition such as abundance, sex proportion, and reproductive condition, together with biological tags (i.e., bat fly prevalence), can provide information about spatiotemporal dynamics of habitats used by bats. In the central part of Veracruz, Mexico, we compared population variables and ectoparasite prevalence of the highland yellow‐shouldered bat (Sturnira ludovici) in two landscapes, one dominated by shade‐coffee plantations and another by forest fragments. Comparing these attributes between these two landscapes will increase our knowledge about the role of this agro‐ecosystem in the conservation of this species, which is an important seed disperser of cloud forest vegetation. Total abundance and proportion of females was greater in forest fragments than in coffee plantations, whereas the percentage of reproductive females and bat fly prevalence was similar between landscapes. Our results show that landscapes with forest fragments harbor the greatest abundance of S. ludovici, but shade‐coffee plantations also are utilized by S. ludovici and likely adjacent forest remnants provide enough food resources for this species and other frugivores. Moreover, this study provides more evidence documenting the importance of preserving the last cloud forest fragments in the central region of Veracruz, Mexico, and suggests that using shade‐coffee plantations to connect forest fragments may be an effective way of maintaining populations of S. ludovici and likely other volant frugivores.